GISClient: la soluzione adatta per la rete (GEOmedia, 2009)
GisClient: the internet GIS solutionGisClient is a web applications that allows the management of complex GIS projects, through the use of simple features. In addition to configuring the map, provides powerful tools for managing and analyzing data, all through graphical interface. Many public and private has adopted it as standard for theirprojects. The stable version is 2.0.12, used on server Linux an Windows, is released under GNU/GPL3.